STUDENT'S ABILITY IN COMPREHENDING READING TEXT AT SMP NEGERI 1 SANGALLA’ - Ines Massoang (Teaching English as a Foreign Language Overseas Journal, 2022)
The objective of this study was to find out about the ability to read comprehension through reading texts such as descriptive texts, narrative texts, and procedures. How far is the ability of grade IX students of SMP NEGERI 1 Sangalla in understanding reading texts? And in what areas do they face difficulties in understanding the reading text In this study, researchers used quantitative research methods. The subjects of this study were grade IX students of SMP Negeri 1 Sangalla'. For data collection, the researcher used a written test instrument in the form of multiple choice consisting of descriptive, narrative, and procedure reading texts. The researcher used a random sampling technique because the number of class IX students was quite large, the researcher took 20 students as a sample. Based on the results of the study, the researchers found that the ability of the IX grade students of SMP Negeri 1 Sangalla' in understanding descriptive reading texts was 71.25 and included in the good category. However, they have difficulty determining the topic in understanding the descriptive reading text. For students' ability to understand narrative reading texts is 64.6 and is included in the sufficient category. Their difficulty is determining the reference word in a reading text. The student's ability to understand the procedural reading text is 77.15 and is included in the good category. However, their difficulty is determining the topic in the reading.